Output-Based Education : The Evolution of Contracts for Schools in the U.K. - Goldstone, David (World Bank, Washington, DC, 2012)
The private sector has provided investment funding and services for the United Kingdom public sector schools through output-based contracts since 1996. Under these contracts firms provide accommodation and related services, while teachers, still employed by the public sector, provide the core education services. Firms bid their lowest prices, and payments to the winning bidder begin only when services become available at the defined standards. The contracts have evolved from building new schools, to bundling maintenance and rehabilitation across many schools, to setting up information technology facilities under contracts incorporating learning targets for students.